Oxygen cost of sprint training - Berg, K.; Buresh, R.; Parks, L.; Kissinger, K.; Karasek, D.; Sinnett, A.; Trehearn, T. (The Journal of Sports Medicine and Physical Fitness, 2010)
AIM: The purpose of the study was to profile the oxygen uptake of sprinters during various portions of a typical sprint training workout. METHODS: This was a descriptive study of 11 female sprinters and jumpers on an NCAA Division II university track team. Subjects were assessed for VO2max, and VO2 and HR kinetics during a 65 min typical sprint training session on a treadmill. The sprint session included a warm-up, static stretching, acceleration runs, 8x20 s sprints at 150% of velocity VO2max (vVO2max) with a 3-min walk recovery, and a cool-down. RESULTS: Mean VO2 and HR (M±SD) for the entire 65 min sprint training session were 19.1±7.6 mL/kg/min and 138.7±24.0 b/min, respectively. VO2 rose to 33 mL/kg/min during and immediately following each 20 s sprint which represented 73% of VO2max. VO2 during and after each sprint remained nearly constant (P>0.05) rather than rising as hypothesized. CONCLUSION: VO2 during a 65 min sprint training workout in female college athletes varies greatly but was elevated to 33 mL/kg/min following each 20 s sprint. VO2 did not rise across the series of eight sprints. These results suggest that chronic sprint training may elicit a moderate aerobic training effect. Implications for training are discussed.